A new indole alkaloid with HUVEC proliferation activities from Nauclea officinalis. Issue 18 (17th September 2021) - Mai, Shi-Ying; Li, Yong-Hui; Zhang, Xu-Guang; Wang, Yi-Ran; Zhang, Jun-Qing; Jia, An
Abstract: A new indole alkaloid, namely naucleofficine H (1 ), was obtained from the aqueous extract of Nauclea officinalis, together with four known alkaloids, vincosamide (2 ), strictosamide (3 ), angustoline (4 ) and pumiloside (5 ). Their structures were characterized by analyzing their physicochemical data including NMR, and HRMS. In addition, five compounds were tested for their proliferation activities. The expression of vascular endothelial growth factor (VEGF), extra-cellular signal-regulated protein kinase 1 and 2 (ERK) and phosphorylation of ERK 1/2 (p-ERK) were also detected in HUVEC treated withbioactive compounds using western blotting. The result showed that these compounds could promote HUVEC cell proliferation. Compounds 3 and 5 could up-regulate VEGF and p-ERK in HUVEC. Graphical Abstract: